BIMBINGAN KELOMPOK TEKNIK SELF INSTRUCTION UNTUK MENINGKATKAN DAYA JUANG MAHASISWA YANG KULIAH SAMBIL BEKERJA - Khairat Hsb, Fitri Husaibatul (Institut Daarul Qur'an Jakarta, Indonesia, 2020)
The aim of this research is to test the effectiveness of group guidance using self-instruction technique in order to increase students’ adversity quotient. Adversity quotient is an ability to survive in facing life’s obstacles, it is also a self- developing process, and achieving one’s objective. Self-instruction is a method to transfer ability to individuals using self-verbalization (substituing negative minds with positive minds). This research used quantitative approach with quasi experimental research design, non-equivalent pre-test and post-test control group design. The research conducted in Universitas Pendidikan Indonesia by taking active students whose also have a job as the research subject. The subjects are chosen randomly by considering their age. The subjects must be includes in the age of development, or in other word, 18-25 years old. Research instrument used in this research is the development of Adversity Response Profile (ARP) quick take. Empirically, result of this research shows that self-instruction counseling group is able to increase students’ adversity quotient, shown by statistical data testing and qualitative data from students’ response in the form of worksheet and daily journal. Recommendations from this research are addressed to college counselor in order to be able to implement self-instruction counseling group in the university and to adjust the development of self-instruction counseling group based on students’ need, also for further research to be able to develop a novel research of self-instruction and adversity quotient that is comprehend with this research’s findings.